ELEMENTAL CHARACTERIZATION OF POTENTIAL ATMOSPHERIC DUST SOURCES OF VICTORIA LAND (ANTARCTICA, ROSS SEA SECTOR) BY NEUTRON ACTIVATION - BACCOLO, GIOVANNI; Baroni, Carlo; Clemenza, Massimiliano; Delmonte, Barbara; Maggi, Valter; Motta, Alessandra; Nastasi, Massimiliano; Previtali, Ezio; Salvatore, Maria Cristina (2014)
Recent investigations carried out on the Talos Dome ICE core (TALDICE) revealed the presence of a local fraction of mineral dust entrapped in the ice [1-4]. Several evidences point to the ice-free areas of Victoria Land as possible sources. Here the elemental composition of 40 samples of mineral sediments collected in correspondence of ice-free areas of the Victoria Land is presented [5]. The geochemistry of samples was determined by Instrumental Neutron Activation Analyses (INAA), which allowed quantifying the concentration of 36 elements, spanning from major to trace elements. Two different sample irradiations and 5 data acquisitions were necessary to measure the maximum number of elements. Geochemical results and principal components analyses suggest that the most discriminating elements are the rare earth elements (REE) and incompatible/compatible ones in respect to iron, in accordance with the different lithological composition of the samples. Evidences of chemical weathering were also recognized despite the extremely cold and dry climate of these areas. The characterization of the Antarctic potential source areas of atmospheric dust is the first step in order to identify the active source areas in respect to Talos Dome and to reconstruct the atmospheric trajectories followed by air masses in the different climatic periods.